Granulomatosis with Polyangiitis Presenting as Pyrexia of Unknown Origin, Leukocytosis, and Microangiopathic Haemolytic Anemia - Sima Terebelo; Iona Chen (Case Reports in Rheumatology)
A 66-year-old woman presented to the Emergency Department with a florid sepsis-like picture, a two-week history of fever, relative hypotension with end organ ischemia (unexplained liver enzyme and troponin elevations), and nonspecific constitutional symptoms. She was initially found to have a urinary tract infection but, despite appropriate treatment, her fever persisted and her white blood cell count continued to rise. During her hospitalization the patient manifested leukocytosis to 47,000 WBC/μL, ESR 67 mm/hr (normal range 0–42 mm/hr), CRP 17.5 mg/dL (normal range 0.02–1.20 mg/dL), and microangiopathic haemolytic anemia, with declining haemoglobin and haematocrit. An infectious aetiology was not found despite extensive bacteriologic studies and radiographic imaging. The patient progressed to acute kidney injury with “active” urinary sediment and proteinuria. Kidney biopsy results and serological titres of myeloperoxidase positive perinuclear-antineutrophil cytoplasmic antibodies (MPO+ p-ANCA) led to a diagnosis of granulomatosis with polyangiitis. Immunosuppressive treatment with high dose methylprednisolone and rituximab led to resolution of the leukocytosis and return of the haemoglobin and haematocrit values toward normal without further signs of hemolysis.